The Change of Haemoglobin Levels in Hemodialysis Patient with The Provision of Nutritional Support - Fery Lusviana Widiany; Ari Tri Astuti (JURNAL NUTRISIA, 2020)
Background : Hemodialysis patients are at risk of anemia, malnutrition, and gastrointestinal disorders. Because of those many nutritional problems, hemodialysis patients need to obtain nutritional support of protein sources, which can be filled with catfish (Clarias sp.) abon. Objectives : This study aimed to determine the change of hemoglobin level in hemodialysis patients with the provision of nutritional support. Method : This was a quasi-experimental with the pre-post test design. The study was conducted at Panembahan Senopati General Hospital in Bantul during January–December 2017. Catfish abon was given to the eligible patients approximately 0.36 g/kgBW/day for 21 days. Subjects were 32 routine hemodialysis patients whose age are >18 years. The dependent variable was hemoglobin level, while the independent variable was the provision of catfish abon. Data were analyzed using univariate and bivariate with paired T-test. Results : The average of pre and post intervention hemoglobin level were 9.24±SD g/dl and 9.50±SD g/dl respectively. There were no differences on average hemoglobin level of hemodialysis patient (p=0.208). Conclusion: provision of nutritional support increases the average of hemoglobin level during the intervention, although it does not statistically affect the hemoglobin level of hemodialysis patients.